Система стандартизации в Украине - Vasiljeva, L. P. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
An overview is given of the standardization system that has developed in Ukraine up to the present time. The role of introducing international standards and harmonizing national standards in improving the quality of industrial products, increasing export potential, and maintaining the competitiveness of Ukrainian goods in the global market is demonstrated.